Attitudes towards change and organizational performance: A conceptual discussion - Zakaria, Ashiah; Abdullah, Haim Hilman (UUM College of Business, 2018)
Employees’ attitudes towards change and organizational performance are extremely interrelated each other hence approving that the performance of organization is exaggerated through the attitudes of employees towards change.The literature shows that successful organizational change and performance are determined by the willingness to embrace change. Thus, the purpose of this paper is to discuss the conceptualization of change attitudes including readiness and openness towards change, and cynicism about organizational change in responding to change initiative which therefore impacts the outcomes and performance of organization.